Some Observations on the Language of Modern Polish Youth Subculture - Marczewska, Marzena (Respectus Philologicus, 2006)
The paper discusses the impact of both the lnternet slang and hip-hop slang on the everyday language used by young Poles. This influence makes the generation gap more and more distinct as young people have created their own "secret code" that allows them to communicate within their closed society. The article presents vocabulary that is typical of hip-hop fans and the lnternet users in Poland.